Effect of weaning age and solid feed distribution before weaning on performances and caecal traits of young rabbits - Piattoni F.; Maertens L. (2. International Conference on Rabbit Production in Hot Climates, 1999)
The effect of early weaning and dietary shift from milk to milk and pellets, at different ages, on growth performances and ontogenic factors of young rabbits, was studied. Fifteen conventional litters, of 8 young each, were allotted to five experimental groups (A; B; C; D; E). Weaning was performed at the age of 18 days for treatment A or at the age of 32 days for the others. The latter received pellets at the age of 18 (B), 22 (C), 25 (D) and 28 days (E), respectively. Milk intake and pellet intake, separately from their mother, was measured daily. Out of each litter one young rabbit was sacrificed at the age of 22; 25; 28; 31, 35, 42 and 56 days, to determine caecum weight and biochemistry. Both weaning age and solid feed distribution affected significantly growth performances and caecum development. Early weaned young (A) showed a significantly lower DWG between 18 and 22 days of age (P<0.01). However, afterwards they recovered and showed a comparable DWG with treatments receiving milk and pellets. Late distribution of solid feed (C, D and E young) resulted in a significant lower LW at weaning, compared to early feed distribution (B-litters)(P<0.01). At 32 days, LW was, for treatment A to E, 671; 783; 597; 697 and 579 g/young, respectively. The development of the caecum (as per cent LW) and the drop of caecal pH was clearly related to the intake of solid feed. Treatment A showed always the highest caecum weight, paralleled by the lowest pH, especially before 28 days of age.
2. International Conference on Rabbit Production in Hot Climates, 1998/09/07-09, Adana (Turkey)